Primary cilia regulate hematopoietic stem and progenitor cell specification through Notch signaling in zebrafish - Zhibin Liu (Nature Portfolio, 2019)
Haematopoietic stem and progenitor cells (HSPCs) produce all blood lineages and arise from the haemogenic endothelium (HE) during embryogenesis. Here the authors show that genes specific to cilia formation are required for HSPC development in the HE in zebrafish through transduction of Notch signal.